EFFECTS OF POSITIVE EMOTIONS, ACADEMIC SELF EFFICACY AND SELF REGULATED LEARNING ON SATISFACTION WITH LIFE IN MEDICAL STUDENTS - Bilal, Ahmad; Umair , Muhammad; Muhammad Ateeb; Alina Saif (Journal of University Medical & Dental College, 2021)
ABSTRACT BACKGROUND & OBJECTIVE: The previous studies had found a significant relationship among positive emotions, academic self-efficacy (ASE), self-regulated learning (SRL), and satisfaction with life (SWL). The present study was conducted to predict SWL from positive emotions and SRL in medical students. METHODOLOGY: The study involved a cross-sectional survey research design. Three hundred medical students from the three medical colleges in Bahawalpur, Lodhran, and Sahiwal were randomly recruited to participate in the study from October 2019 to January 2020. Research Ethics Committee duly approved the study at The Islamia University of Bahawalpur vide No. REC/B-31/2019-F. All the participants filled the necessary informed consent form. Four Likert type scales (a) Dispositional Positive Emotions Scale, (b) Academic Self Efficacy Scale, (c) Efficacy for Self Regulated Learning Scale, and (d) Satisfaction with Life Scale were appended to a single questionnaire to collect the data. The Statistical Package for the Social Sciences, version 25, was used for statistical analysis. The correlation analysis, multiple regression analysis, and analysis of variance were used to compute results. RESULTS: The study found a statistically significant positive correlation among positive emotions, ASE, SRL, and SWL in medical students. The positive emotions and SRL significantly predicted SWL while ASE did not significantly predict SWL in medical students. The 4th and 5th-year students showed more positive emotions, and students of 1st and 4th years showed more SRL than students of other years. CONCLUSION: The study concluded that both positive emotions and SRL significantly predicted SWL in medical students. There were found significant year-wise differences in both positive emotions and SRL.